2022
DOI: 10.3389/fendo.2022.815968
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Androgen Excess-Related Metabolic Disturbances on Granulosa Cell Function and Follicular Development

Abstract: Polycystic ovary syndrome (PCOS) is a common reproductive endocrine disease in women of reproductive age. Ovarian dysfunction including abnormal steroid hormone synthesis and follicular arrest play a vital role in PCOS pathogenesis. Hyperandrogenemia is one of the important characteristics of PCOS. However, the mechanism of regulation and interaction between hyperandrogenism and ovulation abnormalities are not clear. To investigate androgen-related metabolic state in granulosa cells of PCOS patients, we identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 51 publications
0
23
1
Order By: Relevance
“…4 d). This result contrasts with the one published by Liao et al [ 34 ], in which the authors demonstrated that 15-LOX expression was up-regulated in GCs isolated from women with PCOS. In regard to COV434 cells, a significant increase in 15-LOX expression is observed when these cells are also exposed to CMs of M1 and M2 macrophages (Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…4 d). This result contrasts with the one published by Liao et al [ 34 ], in which the authors demonstrated that 15-LOX expression was up-regulated in GCs isolated from women with PCOS. In regard to COV434 cells, a significant increase in 15-LOX expression is observed when these cells are also exposed to CMs of M1 and M2 macrophages (Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…[30] Additionally, androgen exposure significantly affects the metabolic state of GCs in PCOS women, and impairs follicular growth and oocyte maturation, while the potential molecular mechanism remains to be explored in the future. [31] Moreover, the endocrine and ovulatory disturbances observed in PCOS exist on a continuum, with a milder phenotype of elevated androgen and follicles evident in eumenorrheic women with oligo-ovulation, which is indicative of factors that exist along a continuum of testosterone levels, including those without clinical hyperandrogenism (HA). [32] In parallel, a proof-of-concept study proposes that menstrual shedding may improve endometrial progesterone sensitivity, general endometrial function, and, possibly, pregnancy outcomes, in women with PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…For this, alginate-encapsulated mouse secondary follicles were treated with 10 µM dehydroepiandrosterone (DHEA) to simulate the hyperandrogenic environment characteristic of PCOS. Their findings revealed that excessive androgen concentrations blocked follicular growth, cumulus expansion and ovulation in vitro [79]. These effects were associated with impaired steroidogenesis and reduced lipid metabolism in granulosa cells.…”
Section: Modelling Polycystic Ovary Syndrome (Pcos)mentioning
confidence: 98%
“…Traditionally, animal models, such as dihydrotestosterone (DHT)-induced PCOS mice, or 2D culture of granulosa cells isolated from PCOS patients have been used to study the effects of elevated androgen levels on the ovary and specifically on the granulosa cells [77,78]. Recently, Liao and colleagues used ovarian organoids to investigate the metabolic effects of androgen on granulosa cells during follicular growth [79]. For this, alginate-encapsulated mouse secondary follicles were treated with 10 µM dehydroepiandrosterone (DHEA) to simulate the hyperandrogenic environment characteristic of PCOS.…”
Section: Modelling Polycystic Ovary Syndrome (Pcos)mentioning
confidence: 99%